Clinically Meaningful Responses to Dupilumab Among Children Aged 6 Months to 5 Years with Moderate-to-severe Atopic Dermatitis who did Not Achieve Clear or Almost Clear Skin According to the Investigator’s Global Assessment: A Post Hoc Analysis of a Phase 3 Trial - Michael J. Cork; Benjamin Lockshin; Andreas Pinter; Zhen Chen; Brad Shumel; Randy Prescilla (Acta Dermato-Venereologica, 2024)
In young children, atopic dermatitis (AD) imposes a multidimensional burden on many aspects of their quality of life (QoL) and that of their families. LIBERTY AD PRESCHOOL part B was a randomized, double- blinded, placebo-controlled phase 3 trial in 162 children (aged 6 months to 5 years) with moderate-to- severe AD receiving dupilumab or placebo, plus low-potency topical corticosteroids. Post hoc analyses were performed on the full analysis set (FAS) and a subset of patients with Investigator’s Global Assessment score > 1 at week 16. The primary outcome was the proportion of patients at week 16 achieving a composite endpoint encompassing clinically meaningful changes in AD signs, symptoms and QoL: ≥ 50% improvement in Eczema Area and Severity Index; and/or ≥ 4-point reduction in worst scratch/itch numerical rating scale; and/or ≥ 6-point reduction in Children’s Dermatology Life Quality Index/Infants’ Dermatitis Quality of Life Index. Significantly more patients receiving dupilumab vs placebo achieved the composite endpoint in both the FAS (77.7% vs 24.6%, p < 0.0001) and subgroup (68.9% vs 21.5%, p < 0.0001). Dupilumab provided rapid and significant, clinically meaningful improvements in AD signs, symptoms, and QoL in the overall group and subgroup of patients who did not achieve clear or almost clear skin at week 16.